Association of diabetes mellitus with postoperative opioid consumption in patients undergoing primary unilateral hip arthroplasty. Issue 3 (March 2021) - Regnier, Shane M; Khatibi, Bahareh; Gabriel, Rodney A
Opioids are an indispensable component of perioperative pain management; however, the burgeoning opioid epidemic necessitates research into the risk factors for the development of opioid dependence and abuse following surgery. Diabetes has been identified as a risk factor for prolonged opioid utilisation following non-orthopaedic surgery; however, this association has not been investigated following orthopaedic surgery. To bridge this gap in the literature, we performed a retrospective propensity-matched cohort study in patients undergoing primary unilateral total hip arthroplasty. Propensity-matched cohorts were created to compare patients with and without preexisting diabetes mellitus. Outcomes of interest were opioid utilisation and subjective pain on postoperative day 1. Our results did not identify an association between preexisting diabetes and postoperative pain or opioid utilisation. While this study did not identify an association between diabetes and opioid utilisation following total hip arthroplasty, future studies should pursue a prospective, longitudinal approach and investigate other common orthopaedic procedures.